Promoting Health for a vulnerable Family with Relationship Challenges. Exploring the Community Nurse’s Role - Nikolaou, Alexis; Argyriadi, Agathi; Argyriadis, Alexandros (Health & Research Journal, 2024)
Background: In today’s dynamic social landscape, families often encounter a myriad of challenges that can impact their overall health and well-being. Among these challenges, relationship difficulties within the family unit stand out as a significant concern, with potential repercussions for the physical, emotional, and psychological health of its members. Aim: This case study article delves into the intricate dynamics of promoting health within a vulnerable family facing significant relationship challenges. The focus of this study is to explore the pivotal role of the community nurse in addressing the unique needs of such families. Materials and Methods: A qualitative research approach was employed to comprehensively investigate the experiences of a vulnerable family navigating relationship challenges. Data collection involved in-depth interviews, direct observations, and document analysis. Thematic analysis was used to extract meaningful patterns and insights from the collected data. Results: The findings underscored the crucial influence of the community nurse in fostering the health and well-being of the vulnerable family. Through tailored interventions, collaborative support, and sensitive communication, the community nurse played a pivotal role in addressing the family’s relationship challenges and promoting their overall health. Conclusions: This study sheds light on the significance of the community nurse’s involvement in enhancing the health outcomes of families facing relationship challenges. The role of the community nurse emerges as an essential component in fostering resilience and facilitating positive changes within the family unit.